ANALISIS PERTANGGUNGJAWABAN TERHADAP PELAKU TINDAK PIDANA KEMIGRASIAN TIDAK DAPAT MENUNJUKKAN DOKUMEN PERJALANAN DI INDONESIA - Sinaga, Hasudungan (IBLAM LAW REVIEW, 2023)
Immigration crimes are acts of deviation and violations in the immigration sector where these deviations and violations in the immigration sector can be prosecuted through immigration action or through the judicial process. One form of criminal violation in the immigration sector as mentioned above is the crime of misuse of a residence permit without being able to show travel documents in Indonesia. The results of the research are the factors that cause the immigration crime of not being able to show travel documents/residence permits in Indonesia, including legal substance factors, legal structure factors, and legal culture factors. Law enforcement efforts carried out by the TPI Bandar Lampung Class I Immigration Office against perpetrators of immigration crimes who cannot show travel documents/residence permits in Indonesia can be carried out through Immigration Administrative Actions (actions without the application of criminal sanctions) and Pro Justiciary Actions (judicial processes). The responsibility for perpetrators of migration crimes who cannot show travel documents in Indonesia is in accordance with Decision Number: 05/PID.R/2018/PN.Tjk, namely that the perpetrator must be held accountable for his actions because he cannot show travel documents with a fine of Rp. 1,000,000,- (one million rupiah), subidair imprisonment for 7 (seven) days. The advice given is that it is necessary to increase the number of Immigration PPNS to monitor the presence of foreigners in Lampung Province and increase public legal awareness regarding indications of residence permit violations committed by foreign nationals in the Lampung Province area.